Defect liability period / Muhamad Zairi Hamdan - Hamdan, Muhamad Zairi (Universiti Teknologi MARA, Perak, 2022)
Defect liability period is the period contractor is liable to make good of the defects but how reasonable is the defects liability period to allow defects (patent and latent) This report the occurrence of defects during and after the defect liability period and the contractual terms of defects Malaysia, Malaysia were chosen as case study areas. Findings from the study revealed that 6months defects liability period practice in Malaysia is reasonable enough to allow defects to manifest within the period. whereas most of the defects manifestation often occur after the 3 months defect liability period which really poses a major threat on employers and amount to economic loss. The study suggests extension of defects liability in Malaysia so as to allow the employer to have value for money invested.